DOI: 10.31274/rtd-180813-9297
|View full text |Cite
|
Sign up to set email alerts
|

Strength, ultrasonic and metallurgical evaluation of diffusion bonds of dissimilar materials

Abstract: INFORMATION TO USERSThis manuscript has been reproduced from the microfîhn master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Ojard, et. al, reported that as the bond strength drops from the highest value achieved to approximately half the maximum strength in copper/copper bonds, the IBS value increased by a factor of five (9). The beryllium-copper bond data did not exhibit this sensitivity; however, Ojard's data was based on a limited sample set of only four.…”
Section: Bond Strength Versus Integrated Backscatter and Tof Variancementioning
confidence: 99%
See 2 more Smart Citations
“…Ojard, et. al, reported that as the bond strength drops from the highest value achieved to approximately half the maximum strength in copper/copper bonds, the IBS value increased by a factor of five (9). The beryllium-copper bond data did not exhibit this sensitivity; however, Ojard's data was based on a limited sample set of only four.…”
Section: Bond Strength Versus Integrated Backscatter and Tof Variancementioning
confidence: 99%
“…al. also reported success in utilizing the normalized energy calculations on dissimilar bonds of copper/nickel; however, the single frequency reflection coefficients were unsuccessful in correlating with bond strength (4,9). A novel approach was reported by Nieters et.…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation